Issues of Hazardous Materials Transport and Possibilities of Safety Measures in the Concept of Smart Cities - Adamec, Vladimír; Schüllerová, Barbora; Adam, Vojtěch; Semela, Marek (EAI Endorsed Transactions on Smart Cities, 2016)
The transportation of goods and supplies is an essential part of maintaining a functioning urban infrastructure. It also involves the transport of dangerous goods. This type of transportation may especially in the urban areas signify a high risk that may significantly damage the critical infrastructure of the city if there is an accident and leakage of dangerous chemical substances. The aim is, therefore, to minimize the risk and its consequences. The effective instruments are through the identification, analysis and assessment of these risks, searching for critical areas in cities and ensuring the application of prevention and safety measures. Application of risk analysis methods helps to identify the expected and probable risks that can significantly influence the safety of the critical infrastructure. On the other hand, risk analysis methods which can also identify unknown risks with low probability of occurrence are currently being developed. The paper introduces a methodology of assessment of transport risk in cities focusing on reducing the impact of hazard in cities. The risk analysis methods and approaches are subsequently proposed as the initial stage of implementing the selected safety measures. This paper aims to introduce the issue of risks associated with transportation of hazardous substances in cities and to propose measures that are in accordance with the concept of Smart Cities, in order to contribute to the creation of a functional communication network, traffic flow in cities and increasing the security of critical infrastructure.